2022-RA-1480-ESGO TRANSLACOL project: digital-PCR human papilloma virus (HPV) detection for recurrence prediction in early cervical cancer patients without pelvic lymph node invasion. (20th October 2022) - Macías, Rosa Montero; Robillard, Nicolas; Bruneau, Thomas; Pluvio, Coronado; Boulhic, Mélanie; Frére-Belda, Marie-Aude Le; Stankovic, Ivana; Angeles, Martina Aida; Mery, Eliane; Rigolet, Pascal; Badoual, Cecile; Mathevet, Patrice; et al.
Abstract : Introduction/Background: In early cervical cancer (ECC) patients with nodal metastasis (N+) present worse survival. However, 10–15% of patients without nodal metastasis (N0) present the same survival to N+ patients.As in cervical cancer, HPV DNA could be assimilated to tumoral DNA, we evaluate the presence of HPV DNA in pelvic Sentinel lymph nodes (SLN) by new ultrasensitive droplet-based digital polymerase chain reaction (ddPCR) as a biomarker of survival. Methodology: Inclusion criteria: EEC patients who underwent pelvic SLN detection N0 in pelvic lymph nodes. Associated pelvic lymph nodes samples were available for 60 patients with HPV16, HPV18 or HPV33 positive tumours. In SLN, after DNA extraction, HPV16 E6, HPV18 E7 and HPV33 E6 gene were respectively targeted and detected by ultrasensitive ddPCR optimized on two different platforms, the RainDrop Digital PCR System (RainDance Technologies, Bio-Rad, Hercules, CA) or the Biorad system.We compare two groups according to HPV DNA in SLN: positive or negative. Results: There was no difference between the negative HPV DNA SLN group and the positive HPV DNA SLN group in terms of patients and surgical-pathological characteristics, treatments and time of follow-up. Two patients in negative HPV DNA SLN group and 6 in positive HPV DNA SLN group presented recurrence and the mean time of recurrence was respectively 43.5 and 29.2 month, but, these differences are not statistical significant.However, all of the 4 deaths listed in our study occurred in the positive HPV DNA SLN group for which the 10 years Overall survival (OS) is thus significantly decreased. Conclusion: Our results show worst OS in patients with detected HPV DNA compared to patients without detected HPV DNA in their SLN and the same tendency is observed for PFS without significance. Thus, HPV DNA in SLN detected by ultrasensitive ddPCR could represent an interesting prognosis biomarker in N0 ECC.